2012
DOI: 10.2135/cropsci2011.12.0677
|View full text |Cite
|
Sign up to set email alerts
|

Validation of QTL for Grain Yield‐Related Traits on Wheat Chromosome 3A Using Recombinant Inbred Chromosome Lines

Abstract: Previously, quantitative trait loci (QTLs) for grain yield (GYLD) and yield-related traits were identified by using a population of recombinant inbred chronnosome lines (RICLs) developed from the wheat {Triticum aestivum L.) eultivar Cheyenne (CNN) and its substitution line CNN(WI3A), in which the 3A chromosome of eultivar Wichita (Wl) was substituted for CNN chromosome 3A. Our objectives were to identify and validate the QTL previously identified in CNN(RICLs3A), using the mirror population WI(RICLs3A). A pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 54 publications
3
20
0
Order By: Relevance
“…However, in the present field data analysis a QTL for SPSM was found associated with Xgwm218 . Interestingly, presence of overlapping QTLs identified in the present and the earlier studies was validated by the analysis of the ‘mirror population’, where the QTLs for GVWT, SPSM, and PH were found associated with Xgwm218 [14]. Similarly a QTL for HD in the marker interval wPt2698-wPt2740 was detected using greenhouse data, however no QTL for HD was detected in the same marker interval using the field data.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…However, in the present field data analysis a QTL for SPSM was found associated with Xgwm218 . Interestingly, presence of overlapping QTLs identified in the present and the earlier studies was validated by the analysis of the ‘mirror population’, where the QTLs for GVWT, SPSM, and PH were found associated with Xgwm218 [14]. Similarly a QTL for HD in the marker interval wPt2698-wPt2740 was detected using greenhouse data, however no QTL for HD was detected in the same marker interval using the field data.…”
Section: Resultssupporting
confidence: 77%
“…Localization of these QTLs was later reconfirmed by the use of a mirror population WI(CNN3A) of 90 RICLs [14]. As in previous studies, QTLs for various yield components co-localized to the two chromosomal regions.…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…However, in the present study, three significant QTLs were associated with TKW on chromosomes 2H and 4H, which explained between 5.2 and 5.7% of the phenotypic variation. This result can be explained by TKW being influenced by the environmental conditions that occur during the grain filling period when the crop is more susceptible to drought (Mengistu et al, 2012). The QTL detected for TKW on chromosome 2H at ~45 cM has been reported on a similar position in other studies (Rode et al, 2012;Kalladan et al, 2013).…”
Section: Resultssupporting
confidence: 66%
“…Because the same markers were used in some of those studies, we can compare our results to the previous studies directly. In this study, wmc640‐wmc695 on chromosome 3A was identified as a QTL for PH, which was consistent with the location of QPht.idw – 3A (Campbell et al ; Dilbirligi et al ; Mengistu et al ). The QTL represented by gwm156 controlling PH and GNS was also consistent with a known locus (Table ) (Liu et al ; Maccaferri et al ; Gegas et al ).…”
Section: Discussionsupporting
confidence: 89%